Collective identity and the limits of innovation: a review and research agenda. Issue 1 (2nd January 2021) - Kavanagh, Brian; Perkmann, Markus; Phillips, Nelson
ABSTRACT: In this essay, we discuss how collective identity shapes and constrains innovation in organisations and argue that this phenomenon deserves more attention from innovation scholars. Drawing on the existing literature, we distinguish three mechanisms through which a collective identity affects innovation – top management team cognition and emotion, organisational member resistance, and external stakeholder resistance – and illustrate these mechanisms by drawing on the example of symphony orchestras. Orchestras have faced shrinking audiences and significant declines in revenue for decades, yet their ability to innovate in response has been constrained by the very traditional collective identity of the 'symphony orchestra'. We go on to argue that innovation researchers need to pay more attention to the mechanisms through which collective identity limits and shapes innovation, to investigate potential strategies that organisations can use to manage the tension between collective identity and innovation, and to better understand how collective identity can be used as a resource in innovation.